The Influence of Job Placement and Career Development on Employee Retention at PT Darussyifa Hikmah Tirta - Fadillah, Siti Aulia; Komariah, Kokom; Nurmala, Resa (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the effect of job placement and career development on employee retention at PT Darussyifa Hikmah Tirta. Using a quantitative method with a descriptive and associative approach, data were collected from 63 respondents through questionnaires. Regression analysis results show that job placement and career development significantly influence employee retention. The implication is that companies should align HR management strategies by emphasizing proper placement and career support to enhance retention.